Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1042/bsr20192697
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00668 promotes cell proliferation, migration, invasion ability and EMT process in hepatocellular carcinoma by targeting miR-532-5p/YY1 axis

Abstract: Liver cancer is now one of the most lethal and commonest cancers in the world, among which over 90% is hepatocellular carcinoma (HCC). Recent studies have confirmed long non-coding RNAs (lncRNAs) are implicated in carcinogenesis. It has been reported lncRNA LINC00668 serves as an oncogene in several cancers. However, the mechanism where LINC00668 regulates HCC is still unclear. qRT-PCR analysis was adopted to detect the expression of relative RNAs. Cytoplasmic and nuclear RNA fraction analysis was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…26 In HCC, many researches verified that miR-532-5p was underexpressed in HCC, and it could restrain HCC proliferation, migration and invasion to inhibit cancer development. [27][28][29][30] Similar to these results, our study also revealed that miR-532-5p might play a tumor suppressor role in HCC by inhibiting HCC cell proliferation and metastasis. The reversal effect of anti-miR-532-5p on si-circANTXR1-mediated HCC progression showed that circANTXR1 regulated HCC progression via sponging miR-532-5p.…”
Section: Discussionsupporting
confidence: 79%
“…26 In HCC, many researches verified that miR-532-5p was underexpressed in HCC, and it could restrain HCC proliferation, migration and invasion to inhibit cancer development. [27][28][29][30] Similar to these results, our study also revealed that miR-532-5p might play a tumor suppressor role in HCC by inhibiting HCC cell proliferation and metastasis. The reversal effect of anti-miR-532-5p on si-circANTXR1-mediated HCC progression showed that circANTXR1 regulated HCC progression via sponging miR-532-5p.…”
Section: Discussionsupporting
confidence: 79%
“…27,28 These studies revealed various signaling molecules regulated by miR-532-5p, such as CCR4, RUNX3, RERG, Twist1, YY1, KRAS, and NAP1L1. 22,[24][25][26][27][28] In osteoblasts, parathyroid hormone, an essential regulator for bone remodeling, down-regulated miR-532-5p and released its suppression on matrix metalloproteinase 13. 12 Guo et al reported that miR-532-5p up-regulated in osteoporotic tissues and inhibited osteoblastic differentiation by targeting FOXO1.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream from circSKIL, we identified miR‐532‐5p as a target sponged by circSKIL and also a negative regulator of Notch1. By far, most studies report miR‐532‐5p as a tumor suppressor in the context of cancer 22–26 and occasionally as an oncogene 27,28 . These studies revealed various signaling molecules regulated by miR‐532‐5p, such as CCR4, RUNX3, RERG, Twist1, YY1, KRAS, and NAP1L1 22,24–28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating studies have revealed the involvements of long noncoding RNAs (lncRNAs) in oncogenesis and development of liver cancer, such as gastric cancer associated transcript 3 and LINC00668. 5,6 As a component of lncRNAs, small nucleolar RNA host gene 15 (SNHG15) has been developed as an independent role in predicting prognosis of HCC patients, owing to its excessive expression in disease. 7 Abnormal expression of SNHG15 is indicated to connect with advanced clinicopathological traits and poor prognosis in human cancers.…”
Section: Introductionmentioning
confidence: 99%